Design of a Transverse Flux Permanent Magnet Generator Using a Reluctance Circuit - Becker-Cares, C (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
This work presents an analytical methodology to design a permanent magnet transverse flux generator using a reluctance circuit. Unlike other research, it fully indicates the details to design the rotor, stator, and the air gap of the machine, with all its geometry. In the design section, special considerations to determine the outer diameter of the rotor, and the accompanying pole pitch for the U-cores and I-cores are presented. The proposal of an iterative algorithm using a reluctance circuit to calculate the turns of the armature winding and curved trajectories of flux tubes to model the leakage flux that will allow the synchronous inductance calculation also is presented. The proposed methodology allows determining the performance and the lumped parameters of the generator. Furthermore, it provides evidence that with this design it is possible to select the values of standard voltage for electric generators of this topology. The analytical results of the magnetic flux densities, magnetic flux, lumped parameters, electromotive force, terminal voltage, armature current, power factor, and efficiency are compared with 3D finite element method. Analyzing these results, it is possible to verify the good agreement between them.